Regionale Divergenz: Die Mietpreisbremse und die Gleichwertigkeit der Lebensverhältnisse - Norbert Hiller; Sören Gröbel (Wirtschaftsdienst, 2015)
Die Regionalpolitik hat sich zum Ziel gesetzt, gleichwertige Lebensverhältnisse in Deutschland zu schaffen. Allerdings führt gerade die Mietpreisbremse, die die Wohnkostensteigerungen und damit die Ungleichheit innerhalb der Städte mindern soll, über andere Mechanismen zu mehr Ungleichheit zwischen den Regionen. Die wohnungspolitische Maßnahme verstärkt regionale Divergenzen und steht somit im Widerspruch zu grundlegenden regionalpolitischen Zielen. – – German regional policy has set the goal of creating equal living conditions throughout the country. According to the politicians, rent control should reduce the inequality within cities by stopping increases in housing costs, but it leads to increasing inequality among regions through other mechanisms. Living conditions are determined by local income, local amenities and housing prices, which all in all tend to reach a regional equilibrium. By focusing only on housing prices, this equilibrium is distorted. Hence, the current housing policy strengthens regional divergences and is thus at odds with the basic regional policy objectives.
Keywords: 330